Pengaruh proporsi umbi bit (Beta vulgaris L.) dan buah jambu biji (Psidium guajava L.) terhadap sifat kimia dan organoleptik slice jam - Gultom, Sinta Febriyanti; Handarini, Kejora; Prayudanti, Adhania Andika (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
Slice jam is an innovative product that transforms jam into sheet form, emphasizing practicality. Beetroot is known for its high antioxidant content but is often less favored due to its earthy taste and aroma. To mask this flavor, it is combined with guava, which has a more appealing taste and aroma, as well as a higher vitamin C content compared to other fruits. The aim of this research is to determine the best combination ratio between beetroot puree and guava puree to produce slice jam with favorable chemical test and organoleptic properties. The research method is an experimental laboratory study, using a Completely Randomized Design with one factor consisting of four treatments. The treatments are different ratios of beetroot purÃ©e to guava puree: B1J1 (90% : 10%), B2J2 (70% : 30%), B3J3 (50% : 50%), and B4J4 (30% : 70%). Each treatment is repeated three times. The testing parameters include chemical tests for moisture content, fiber content, total soluble solids, and vitamin C content, as well as organoleptic tests assessing color, taste, aroma, and texture. The best research results were found in the jam slice with a proportion of beetroot and guava puree at 30%:70%. Increasing the proportion of guava puree and decreasing the beetroot puree resulted in higher levels of crude fiber, total dissolved solids, vitamin C content, taste, aroma, color, and texture, but decreased the water content.